Legal Aspects of Firearms Registration in Georgia - Mosulishvili, Amiran (European Scientific Journal, ESJ, 2023)
The aim of the analyzed issues of the paper is to improve the legal regulations regarding the registration of firearms. The subject of research in the work is the registration of firearms, and the object of research is the issue of registration of firearms based on inherited rights. As a result of the research, it is revealed that there are certain legal regulations that should be refined and fully cover the problematic circumstances arising in the case of inheriting firearms. The paper presents and argues specific legislative recommendations, the implementation of which we believe will greatly improve the legal framework, in the event that a citizen inherits a firearm.